Constitutive phosphodiesterase activity restricts spontaneous beating rate of cardiac pacemaker cells by suppressing local Ca2+ releases - Vinogradova, Tatiana M; Sirenko, Syevda; Lyashkov, Alexey E; Younes, Antoine; Li, Yue; Zhu, Weizhong; Yang, Dongmei; Ruknudin, Abdul M; Spurgeon, Harold; Lakatta, Edward G (Circulation research, 2008)
Spontaneous beating of rabbit sinoatrial node cells (SANCs) is controlled by cAMP-mediated, protein kinase A-dependent local subsarcolemmal ryanodine receptor Ca(2+) releases (LCRs). LCRs activated an inward Na(+)/Ca(2+) exchange current that increases the terminal diastolic depolarization rate and, therefore, the spontaneous SANC beating rate. Basal cAMP in SANCs is elevated, suggesting that cAMP degradation by phosphodiesterases (PDEs) may be low. Surprisingly, total suppression of PDE activity with a broad-spectrum PDE inhibitor, 3'-isobutylmethylxanthine (IBMX), produced a 9-fold increase in the cAMP level, doubled cAMP-mediated, protein kinase A-dependent phospholamban phosphorylation, and increased SANC firing rate by approximately 55%, indicating a high basal activity of PDEs in SANCs. A comparison of specific PDE1 to -5 inhibitors revealed that the specific PDE3 inhibitor, milrinone, accelerated spontaneous firing by approximately 47% (effects of others were minor) and increased amplitude of L-type Ca(2+) current (I(Ca,L)) by approximately 46%, indicating that PDE3 was the major constitutively active PDE in the basal state. PDE-dependent control of the spontaneous SANC firing was critically dependent on subsarcolemmal LCRs, ie, PDE inhibition increased LCR amplitude and size and decreased LCR period, leading to earlier and augmented LCR Ca(2+) release, Na(+)/Ca(2+) exchange current, and an increase in the firing rate. When ryanodine receptors were disabled by ryanodine, neither IBMX nor milrinone was able to amplify LCRs, accelerate diastolic depolarization rate, or increase the SANC firing rate, despite preserved PDE inhibition-induced augmentation of I(Ca,L) amplitude. Thus, basal constitutive PDE activation provides a novel and powerful mechanism to decrease cAMP, limit cAMP-mediated, protein kinase A-dependent increase of diastolic ryanodine receptor Ca(2+) release, and restrict the spontaneous SANC beating rate.